Television News in South Africa: Mediating an Emerging Democracy*. - Cottle, Simon; Rai, Mugdha (Journal of Southern African Studies, 2008)
The emergence of democracy in South Africa has given rise to considerable debate and discussion surrounding the renewed role of the broadcasting media. The role of South African television news in enabling and enacting democratic processes, however, remains largely unnoticed and under-theorised. This article reports on recent research that secures added empirical purchase on South African television journalism today and does so by analytically identifying, systematically mapping and pursuing into the production domain the repertoire of communicative frames that characterise contemporary South African television news both within as well as across the daily news programmes delivered by the public broadcaster, SABC, and the private network, eTV. Our findings document that there is considerably more complexity in the field of television news than has so far been acknowledged or explored and these complexities have direct bearing on debates about the establishment and enhancement of 'democracy' in South Africa's diverse, fractured and troubled polity.